KOMUNIKASI INTRAPRIBADI DALAM MEMBENTUK SIKAP PERCAYA DIRI MELALUI NEURO LINGUISTIC PROGRAMMING - Wa Ode Nurul Yani (Dialektika, 2018)
Employers face psychological burdens because there are quite a number of challenges in achieving success, but many entrepreneurs experience failure or bankruptcy. In fact, more failed entrepreneurs than successful entrepreneurs. During life, entrepreneurs always face problems, when one problem is resolved, another problem arises. Problems can destroy businesses that have been built, but problems can also make entrepreneurs stronger when addressing and solving problems. Mind and psychic conditions that decrease due to problems can cause poor performance, a crisis of self-confidence makes work not optimal, so that someone becomes slow in making decisions, afraid of facing risks and pessimistic about the future. In changing this crisis of confidence, it is necessary to change your mind. Neuro Linguistic Programming (NLP) is a self-development training that uses the knowledge of the mind. NLP works through intrapersonal communication through a process of sensation, perception, memory and thinking. NLP is in the human mindset, NLP makes a person able to form self-motivation in changing himself to be happier, more confident, more passionate about pursuing a career, and enjoying life in achieving a better future.